1985
DOI: 10.1038/clpt.1985.189
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-induced skin wheals: A possible model for the study of histamine release

Abstract: We evaluated the ability of morphine to release histamine when injected intradermally in man. Mathematic analysis of the dose-response (wheal) relationship suggested that two different effects were involved. The effect of low doses of morphine (0.05 to 1 microgram) was clearly antagonized by naloxone (0.4 or 1.2 mg im 30 minutes before), whereas the effect of higher doses (5 to 50 micrograms) was not modified. The median effective doses of morphine (ED50) for the low dose range effect were 0.07 +/- 0.01 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, flaring around the methadone site was minimal in the present study, and wheals did not form. The absence of wheals and flares after the methadone iontophoresis (present study) and intradermal injection of alfentanil [10], together with the persistence of these responses to morphine after naloxone administration [7,9,10], suggests that a nonopioid mechanism contributes to the formation of wheals and flares provoked by some m-receptor agonists. This mechanism might involve mast cell degranulation [7][8][9][10] or direct effects on the vascular endothelium [10].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, flaring around the methadone site was minimal in the present study, and wheals did not form. The absence of wheals and flares after the methadone iontophoresis (present study) and intradermal injection of alfentanil [10], together with the persistence of these responses to morphine after naloxone administration [7,9,10], suggests that a nonopioid mechanism contributes to the formation of wheals and flares provoked by some m-receptor agonists. This mechanism might involve mast cell degranulation [7][8][9][10] or direct effects on the vascular endothelium [10].…”
Section: Discussionmentioning
confidence: 97%
“…Cutaneous flares and wheals develop after intradermal administration of m-receptor agonists such as morphine, meperidine and fentanyl [7,9,10]. We previously found that wheals developed routinely when morphine was administered by iontophoresis at half the present dose of methadone (de Silva-Rossdeutscher, unpublished doctoral dissertation, Murdoch University, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies showed that intradermal injections of opioid agonists caused localized itching and histamine wheal‐and‐flare reactions (5). In addition, H1‐antihistamines were effective in relieving the local itch induced by dermal morphine injection (6). It appeared from these studies that histamine release was the cause of opioid‐induced pruritus.…”
Section: Inhibition Of Itch Transmissionmentioning
confidence: 99%
“…Histamine release by morphine is well documented (4,5,6,9). To our knowledge, buprenorphine, which resembles morphine structurally ( Fig.…”
mentioning
confidence: 90%